Annals of Microbiology - Cappitelli, Francesca; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
The aim of Annals of Microbiology is the advancement and dissemination of microbiological knowledge in the general, environmental, ecological (e.g. water, soil ecosystems, cultural heritage sites) and applied (e.g. food and industrial) fields. The methodology is usually derived from the areas of biochemistry, molecular biology, physiology, biotechnology and taxonomy. Papers reporting work on bacteria, fungi, microalgae, and bacteriophages are welcome. The journal addresses researchers from both, academia and industry, working in microbiology, biotechnology or ecology. Annals of Microbiology publishes Original Articles, Reviews and Mini-Reviews, Short Communications, Editorials, and Guidelines. The journal$1 (Bs scope does not include theoretical bioinformatics, medical microbiology or phytopathological microbiology. Originally founded as Annali Di Microbiologia Ed Enzimologia in 1940, Annals of Microbiology, an official journal of the University of Milan, is a well-established microbiology journal and has a long tradition of publishing sound international research. Annals of Microbiology operates a single-blind peer-review system. Articles are reviewed by at least two external referees who are aware of the authors$1 (Bnames and affiliations while the reviewer reports provided to authors are anonymous. Single-blind peer review is the traditional model of peer review.s
Keywords: Microbiology; Microbial genetics; Microbial ecology; Fungi; Mycology; Microbiology; Industrial microbiology; Microbiology; Microbial Genetics; Microbial Ecology; Fungi; Industrial Microbiology